Engaging English- and Spanish-speaking older adults with and without possible cognitive impairment in advance care planning group visits: protocol for the ENgaging in Advance Care Planning Talks (ENACT) randomized controlled trial - Farro, Samantha A.; Juarez-Colunga, Elizabeth; Patel, Chandni; Bettcher, Brianne M.; Haynes, Christine A.; Huebschmann, Amy G.; Nowels, David; Tietbohl, Caroline K.; Shi, Jiayuan; Ritger, Carly; Shanbhag, Prajakta; Resman, Kathleen; et al. (Current controlled trials in cardiovascular medicine, 2025)
Background Advance care planning (ACP) helps patients identify and communicate their preferences for medical care and prepares them for decision-making related to future care. While ACP is recommended for older adults with cognitive impairment, few interventions have been tested in primary care for this population. The ENACT trial tests the efficacy of the ENgaging in Advance Care planning Talks (ENACT) Group Visits intervention, which engages older adults with and without possible cognitive impairment in group medical visits focused on the ACP process. Methods This two-arm randomized trial compares the efficacy of the ENACT Group Visits intervention arm to a control arm at 6-month follow-up. The trial will enroll at least 480 patients across 8 primary care clinics. Notable inclusion criteria include English or Spanish-speaking, age 70 or older, and no ACP documents in the electronic health record (EHR) in the past 2 years. The Montreal Cognitive Assessment screener will be administered at study enrollment to identify whether the participant has possible cognitive imparment. Participants will be randomized 1:1 to the ENACT Group Visits arm or control arm. The ENACT Group Visits intervention entails two group visits, facilitated by multidisciplinary clinic staff. The control arm entails sending ACP materials via mail. The primary outcome is new documentation of ACP in the EHR at 6-month follow-up, and it will be analyzed using logistic regression with random effects for site. Secondary outcomes include patient-level ACP readiness, decision self-efficacy, and quality of communication. The impact of possible cognitive impairment on ENACT intervention efficacy will be examined. Survival analyses will be used to examine time-to-new ACP documentation. Mixed methods, including multiple qualitative methods, will be used to assess acceptability, feasibility, intervention fidelity, and other implementation outcomes of the ENACT intervention among patients with possible cognitive impairment. Discussion This study will determine the efficacy of the ENACT Group Visits intervention among diverse older adults, including those with possible cognitive impairment, as evidenced by increased documentation of ACP in the medical record. If efficacious, primary care clinics may implement this ACP intervention that leverages peer interactions and goal setting to support a person-centered ACP process. Trial registration Clinicaltrials.gov: NCT05421728 . Registered on 13 June 2022.